Impedance spectroscopy, DC polarization, XRD and SEM studies on an ionic liquid based gel polymer electrolyte to be used for dye sensitized solar cells. (March 2017) - Perera, K.; Vidanapathirana, K.
Graphical abstract: Abstract: Dye sensitized solar cells (DSSCs) receive lots of attention as a suitable device in converting sunlight to electricity. A great deal of work has been carried out to develop gel polymer electrolytes (GPEs) and one strategy is introducing ionic liquids (ILs) to eliminate some adverse effects and also to improve ionic conductivity. The composition 15% polyvinylidene fluoride (PVdF): 37% ethylene carbonate (EC): 37% propylene carbonate (PC): 11% 1 butyl 3 methyl immidazolium iodide (IB 3M II) showed the highest conductivity. It was a good anionic conductor. IL has caused reduction of crystallinity which assists to enhance conductivity.